PERAN GURU DALAM MEMBENTUK KARAKTER SISWA KELAS III B UPTD SD INPRES BERTINGKAT KELAPA LIMA 1 - Elisabeth Auni; Rince S.M Benu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to gain a deep and contextual understanding of the role of teachers in shaping the character of grade IIIB students at the UPTD SD Inpres Bertinggi Kelapa Lima 1. This type of research is qualitative research with a descriptive approach, with the research subjects being grade IIIB students and their homeroom teachers. Data collection techniques used in this study were observation, interviews, and documentation. The results of this study indicate that the character of grade IIIB students shows varying results for each indicator. In the discipline indicator, the majority of students (61.1%) are in the agree category. This indicates that students are quite disciplined in participating in learning activities. This discipline is seen from compliance with rules and regularity in learning. In the responsibility indicator, 55.6% of students are in the agree category. This means that most students already have responsibilities in learning, but there are still students who are less active in completing assignments or following directions. On the cooperation indicator, the results show that the majority of students (61.1%) are in the disagree category. This means that students' cooperation skills are still low. Students tend not to be active in group activities, discussions, or communication with friends. Meanwhile, on the social concern indicator, all students (100%) are in the agree category. This shows that students have very good social attitudes, such as helping each other, caring for friends, and having a sense of empathy.